O trabalho com seqüências didáticas no ensino fundamental: reflexões sobre experiências com o gênero de texto narrativa de horror - Cardoso, Chislene Moreira (Universidade do Vale do Rio do Sinos, 2008)
It is held in this work, a reflection on the experience of a systematization of teaching in mother tongue based on the proposal for implementing a didactic sequence (Schneuwly and DOLZ, 2004) that focuses a genre of text. The following is the Interactionism Sociodiscursivo (Bronckart, 2005), which presents the idea that the ownership of various genres text is vital in the process of integration of the individual in social practice. Thus, believes that mastery of different genres is necessary so that the user of a language involved, so active in the community in which word is inserted. The work is didactic sequence with a view to developing a textual genre in a situation of teaching and learning. It is presented as a series of educational activities organized systematically and should focus on a genre at a time. In this case, the narrative was the chosen genre of horror, carried out in two classes of teenagers in 7th grade of elementary school, in a private school and in a state school. The comparison between
Keywords: gênero textual; narrativa de horror; seqüência didática; horror narrative; textual gender; didactic sequence; Letras e Artes; Lingüística